Unveiling forms of participation in the governance of UNESCO world heritage sites - Taormina, Francesca; Bonini Baraldi , Sara (European Spatial Research and Policy, 2022)
This paper focuses on the issues of governance and participation of World Heritage sites. It inquiries how decision-making structures to locally managed World Heritage sites may encompass public participation. Through an in-depth qualitative approach, the paper analyses the World Heritage Arab-Norman Palermo and the Cathedral Churches of Cefalù and Monreale serial site (Italy). By examining the participatory dynamics that occurred during the creation and development of the selected World Heritage serial site, this paper reveals three coexisting forms of participation in WHsite decisions: inter-institutional agreement, social aggregation, and multi-actor collaboration. The main findings suggest that although formal decision-making arenas may be participative weakly, the unpacking of participatory practices in urban spaces uncovers a vibrant scene, as it emerges from the Cassaro Alto and Danisinni districts in the city of Palermo.